Protection And Respect For Teachers - Abdul Azis; Vina Fauziah; Yusti Rahayu; Abdul Basyir (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
In an effort to achieve the goals of national education, the government provides recognition to teachers and lecturers as stipulated in the National Education System Law (Sisdiknas). This recognition serves as an acknowledgment of the vital role educators play as agents of change in society. Teachers who demonstrate high performance and dedication are considered deserving of appreciation due to their significant contributions in shaping the character and intelligence of students. The awarding of honors to outstanding and high-quality teachers is not only a form of motivation but also serves to promote increased professionalism among educators. Such recognition reflects a concrete effort to foster a strong work ethic and moral responsibility in guiding the next generation. As the quality of educators improves, it is expected that the overall standard of national education will also be elevated. In addition to recognition, protection of the teaching profession is equally important. This protection may take the form of legal guarantees, security in carrying out duties, and the safeguarding of professional rights. With such protections in place, teachers can perform their responsibilities with a sense of security and peace of mind, which positively influences their effectiveness and productivity in the learning process. The responsibility of education goes beyond teaching; it also involves the development of students' character and personality. Teachers are expected to guide students to become individuals who are devoted to God Almighty, possess noble character, are responsible, creative, independent, resilient, democratic, and professional in their respective fields. This is part of the broader national vision to enlighten the life of the nation, as mandated by the constitution.